EFFECTS OF INQUIRY ON TRAINING AND CRITICAL THINKING PROCESS SKILL SCIENCE PHYSICS - Tetty Ompusunggu; Betty M Turnip; Makmur Sirait (Universitas Negeri Medan, 2016)
The aims of this research were to analyze the result of student’s Science Process Skills by using Inquiry Training Learning Model, to analyze the result of student’sScience Process Skills who had critical thinking ability above average better than critical thinking ability below average and to analyze the interaction between Inquiry training learning model and critical thinking ability of physics student’s Science Process Skills. This research was a quasi-experimental with two group pretest posttest design and anova design. The sample was conducted by cluster random sampling of two classes, the first class as experiment class with inquiry training Learning Model, and the second class as a control class with Conventional Learning. The research instrument consisted of science process skills test and critical thinking test. Data in this research was analyzed by using two ways Anova. The results of the research showed that student’s Science Process Skills using inquiry training learning model better than conventional learning, student’s Science Process Skills who had critical thinking above average better than critical thinking below average, and there was interaction between Inquiry training learning model and critical thinking to improve physics sudent’s Science Process Skills